Laparoscopic versus conventional open appendicectomy: a prospective comparative analytical study in a tertiary care set up - Shrivastava, Anurag; Jain, Anurag; Jain, Rajiv (International Journal of Research in Medical Sciences, 2019)
Background: Present study outlines the outcomes of laparoscopic appendicectomy compared to open conventional appendicectomy in a tertiary care set up with aim to validate advantages and shortcomings of both procedures. Methods: A series of 80 cases above 18 years of age with clinical diagnosis of appendicitis having Alvarado score of seven and above were studied prospectively under the two groups after proper written consent: Open appendectomy-40 cases, Laparoscopic appendectomy-40 cases. Both groups were compared on grounds of intra-operative complications, additional diagnostic potential, operative time, postoperative analgesia, post-operative complications, length of hospital stay, subjective cosmesis, and return to routine normal activities. Values obtained were statistically analyzed. Results: The median operative time in Laparoscopic Appendicectomy was 58.22 minutes (range 32.68-85.46 min) as compared to open procedure which took 43.65 minutes (30.36-65.48min) (P<0.05). Conversion to open procedure was done in 10% (n=4) of laparoscopic cases. Mean value of postoperative pain by visual analogue scale was low in Laparoscopic Appendicectomy (LA) compared to Open Appendicectomy (OA) (P<0.05). Mean post-operative stay (3.2±0.34 days versus 2.3±0.24 days) and surgical site infection was recorded in 10 patients (25%) in OA group and 5 (13.9%) in LA group (P<0.05). Conclusions: It can be concluded that laparoscopic surgery is safe with greater diagnostic potential for additional pathologies and better Subjective cosmesis . But all these merits were at the price of longer operating time and a specialized set up needed for laparoscopy.